Mothers Use More Structure-Based Feeding in Firstborns Than Secondborn Siblings (P11-117-19). (13th June 2019) - Ruggiero, Cara; Birch, Leann; Paul, Ian; Savage, Jennifer
Abstract: Objectives: To explore the discordance of maternal feeding practices by birth order and weight status between FBs participating in the Intervention Nurses Start Infants Growing on Health Trajectories (INSIGHT) trial and their secondborn (SB) siblings. Methods: Structure and control–based parent feeding practices were assessed at 1 year in FBs and SBs (subscales: limiting exposure to unhealthy foods, consistent meal routines, restriction and pressure to eat). Paired t-tests examined difference scores and correlations were compared between siblings. Subgroup analyses identified siblings that were discordant and concordant on weight status at 1 year (normal weight vs. at risk for overweight defined as weight for length ≥ 85 th percentile, WHO growth charts). Results: 117 sibling dyads participated with SBs (57% female) born 2.5 ± 0.8 years after FBs (53% female). When each assessed at age 1 year, 22% of FBs and 27% of SBs were at risk for overweight. 63% of sibling dyads were both normal weight, 13% were both at risk for overweight, and 24% of siblings were weight status discordant. FB and SB feeding practices were correlated (range r = 0.34-0.64, all P < 0.01). Overall, mothers reported greater use of structure-based practices in FBs compared to SBs: limiting exposures to unhealthy foods (4.05 vs. 3.95, P < 0.01) and consistent meal routines (4.10 vs. 3.98, P < 0.01). Control-based feeding practices (restriction and pressure to eat) did not differ significantly by birth order. No differences existed by weight status (normal vs. at risk for overweight) between discordant pairs. Within sibling pairs that were both normal weight, mothers reported greater use of restriction in SBs compared to FBs (2.23 vs. 2.02, P = 0.01), but not pressure or structure-based practices. No differences in feeding were found in sibling pairs at risk for overweight. Conclusions: SBs may be exposed to more unhealthy foods and have less consistent meal routines due to increased responsibilities of parents with the addition of a second child. Responsive parenting guidance should consider evolving family dynamics, foods provided and feeding practices with increasing family size. Funding Sources: National Institutes of Health.